Detecção de descargas parciais em condutores elétricos utilizando redes de Bragg em fibra ótica - Vendruscolo, Ricardo (2022)
Partial Discharges (PD) are characterized by high voltage signals, which cause current passage through an insulating medium. They occur, generally, by failures at insulating components in medium and high voltage circuits, causing energy leak problems in conductors, connections, inside large engines, transformers, among others. One characteristic of this phenomenon is the attendance of acoustic vibration, beyond the temperature variation in the environment that it occurs. In this work, a study about these characteristics using Fiber Bragg Gratings (FBG) examinated a sampling rate of 6kHz is presented. The measurement was made with a FBG allocated in contact with a 35mm² and XLPE insulating copper cable, exposed to the PD. An experimental arrangement was used to emulate the occurrence of Pds using an ignition coil. Three distances of PD occurrences were emulated: 6mm, 12mm and 18mm. Therefore, three different levels of PD could be monitored by the FBG. It was possible to measure the acoustic vibration variation, which results were between 2 and 15 Micro Strain. Regarding to the temperature, it was possible to measure variations between 0,5ºC and 4ºC. The results imply that the FBG with its sensitivity crossed to temperature and deformation have the capacity of identify the amount of PD existing in the distances od 12mm and 18mm due to the dynamical deformation caused by the PD. It’s also possible to determine the duration of the discharges due to the temperature increase. On the other hand, in the 6mm distance, due to the higher frequency of PD occurrences, it wasn’t possible to identify the PD number, just the temperature increase. Thus, FBGs can be used to detect determined types of Pds, even while operating at an acquisition rate of 6 kHz.